MEDIA PEMBELAJARAN BERBASIS CAI (COMPUTER ASSITED INSTRUCTION) PADA MATA PELAJARAN PPKn SEKOLAH DASAR - Sri Widoyoningrum; Iskandar Wiryokusomo; Sugito Sugito (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The purpose of this development research is to develop a CAI (Computer Assited Instruction) based learning product for PPKn (Pancasila and Citizenship Education) students in grade 1 and 2 elementary schools. The main discussion of PPKn learning materials includes the Pamcasila symbol and the values contained in Pancasila. This development research method uses the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Learning media development instrument products are in the form of validation results for material experts, validation sheets for media experts, validation sheets for field experts (class teachers) and questionnaires for students. The results of the development research resulted in the PPKn learning product being declared to be very suitable for use. It can be seen the results of the percentage acquisition per validator, the results of the validation of media experts obtained 83.33%, the results of the material expert validator obtained 86.67% and the results of the field expert validator (teacher) gained 87.50%. Based on the results of the trial product development of learning media to students is divided into small groups and large groups. CAI (Computer Assited Instruction) based learning media assessment related to the attractiveness of learning media. In the small group the percentage was 88% and in the large group the percentage was 92.44%. It can be concluded that the CAI (Computer Assited Instruction) learning media based on PPKn subjects are declared suitable to be used to support the learning process in Primary Schools